2005
DOI: 10.1002/cbf.1175
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol on rat placenta

Abstract: In this study, daily food and water consumption and body weights, histopathology of placenta, tenascin (TN), type IV collagen and EGF and its receptor immunolocalization in the placenta of albino rats treated with two doses of alcohol (1 and 5 g kg(-1) day(-1)) were determined. Alcohol was administered in three different periods i.e. the whole 4 weeks before the pregnancy, during the pregnancy, and during the 4 weeks before the pregnancy plus pregnancy itself. The samples of placenta obtained from control and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Decidual diameter was decreased in certain regions. Placental hypertrophy has been reported as a compensatory reaction to intrauterine growth restriction (IUGR) under an unfavorable maternal environment such as maternal hemorrhage [72], uterine vessel ligation [73], and indomethacin [74] or ethanol exposure [75]. …”
Section: Discussionmentioning
confidence: 99%
“…Decidual diameter was decreased in certain regions. Placental hypertrophy has been reported as a compensatory reaction to intrauterine growth restriction (IUGR) under an unfavorable maternal environment such as maternal hemorrhage [72], uterine vessel ligation [73], and indomethacin [74] or ethanol exposure [75]. …”
Section: Discussionmentioning
confidence: 99%
“…The average peak blood acetaldehyde concentration is in the range 26–43 µM [12], [15], [16], [34], [42], [43]. Pharmacological studies in animals have used as much as 50–100 mM ethanol administered daily [19]. We have shown that ethanol or acetaldehyde at clinically relevant concentrations (≤40 mM and ≤40 µM respectively) has adverse effects on two key aspects of trophoblast function: proliferation and nutrient transport.…”
Section: Discussionmentioning
confidence: 99%
“…Placental development is significantly altered with increased placental weight in rats following chronic high ethanol (20%v/v) liquid diet [19], [23], [24]. This increase is accompanied by trophoblast morphological irregularities and altered blood vessel development in the nutrient-exchanging labyrinth zone [19]. In sheep on a high ethanol diet, placental transport of system A-dependent α-amino isobutyric acid is reduced [25].…”
Section: Introductionmentioning
confidence: 99%
“…In spontaneously hypertensive rats, it is induced in response to a poor capacity of the uteroplacental unit for transferring glucose to fetuses 38 . Drug- and chemical-induced compensatory placental hypertrophy is reported in indomethacin-exposed rats 39 and ethanol-exposed rats 40,41 . Secondly, placental hypertrophy is detected in the intact uterus with a decreased number of corpora luteum, implantation sites and fetuses (less than six fetuses in rats) 42 as an implantation-related reaction.…”
Section: Histopathology Of the Placenta In The Ratmentioning
confidence: 99%
“…14). In animal experiments, placental necrosis is induced by such things as valproate acid 50 , chlorpromazine 51 , glucocorticoid 52 , streptozotocin 53 , cadmium 54 , ethanol 40 , lead acetate 55 , diethylstilbestrol, estrogen, tobacco, adrenomedullin antagonist, cocaine and vitamin E-deficiency. Histopathologically, placental necrosis appears more commonly in the trophoblasts in the labyrinth zone.…”
Section: Histopathology Of the Placenta In The Ratmentioning
confidence: 99%